The quest for wheat flour alternatives : sensory characterisation and volatile compound profiling of composite flours and flatbread from sorghum, cassava and cowpea flours - De Kock, Henrietta Letitia (University of Pretoria, 2024)
Thesis (PhD (Food Science))--University of Pretoria, 2023.